Evaluation of Cases Presenting to a University Hospital Psychiatry Clinic for the Determination of Disability: Psychiatric Diseases and Disability - Çelikbaş, Zekiye; Batmaz, Sedat; Aslan, Esma Akpınar (The Bulletin of Legal Medicine, 2021)
Objective: In this study, sociodemographic characteristics and diagnoses of patients who presented to Tokat Gaziosmanpaşa University School of Medicine Department of Psychiatry for disability evaluation and who were confirmed to be psychiatrically disabled. Method: The files of the patients who presented to the health board for disability determination between 01.01.2019-31.12.2019 were reviewed retrospectively. Descriptive statistical analyses were performed for demographic and clinical data. Results: There were 494 patients over the age of 18 who presented for disability determination. It was concluded that 43 of 157 cases with psychiatric diagnosis at the time of presentation were confirmed to be disabled. The average age of these cases was 42.56 ± 8.50 years and 37 (86%) were male. The most common diagnosis of disability was mental retardation with an of IQ 50 and below (n = 18, 41.86%) and schizophrenia and its subtypes (n = 12, 27.9%) unable to be employed despite treatment. Conclusion: The results of our study will guide future studies on the recognition of mental disorders that result in disability and adversely affect the employment and to bring these patients back into employment.